Sekularisme dan Pendidikan Akhlak: Studi Pemikiran Syed Muhammad Naquib Al-Attas tentang Konsep Pendidikan Akhlak dalam Menghadapi Sekularisme - Anugrah, Dena Sri; Syahidin, Syahidin (Universitas Pendidikan Indonesia, 2024)
This article aims to understand the concept of moral education in facing the impact of secularism, namely the loss of manners, according to Syed Muhammad Naquib al-Attas. This study is meaningful in answering the problem: What is Syed Muhammad Naquib al-Attas's educational concept in facing secularism? This problem is discussed through a literature review whose data is obtained from various works of Syed Muhammad Naquib al-Attas which relate to Secularism and the concept of moral education. All research data was analyzed using the content analysis method. This study shows that according to Syed Muhammad Naquib al-Attas secularism is an ideology that separates worldly life from ukhrawi life, resulting in the destruction of aqeedah which results in the loss of manners. While education is one way to improve morals. According to Syed Muhammad Naquib al-Attas, moral education is not only centered on understanding, but also on practice and habituation in everyday life.